Sex-Related Differences in Innate and Adaptive Immune Responses to SARS-CoV-2 - Agrawal, Sudhanshu; Salazar, Jon; Tran, Thu Michelle; Agrawal, Anshu (Frontiers in Immunology, 2021)
Coronavirus disease 2019 (COVID-19) exhibits a sex bias with males showing signs of more severe disease and hospitalizations compared with females. The mechanisms are not clear but differential immune responses, particularly the initial innate immune response, between sexes may be playing a role. The early innate immune responses to SARS-CoV-2 have not been studied because of the gap in timing between the patient becoming infected, showing symptoms, and getting the treatment. The primary objective of the present study was to compare the response of dendritic cells (DCs) and monocytes from males and females to SARS-CoV-2, 24 h after infection. To investigate this, peripheral blood mononuclear cells (PBMCs) from healthy young individuals were stimulated in vitro with the virus. Our results indicate that PBMCs from females upregulated the expression of HLA-DR and CD86 on pDCs and mDCs after stimulation with the virus, while the activation of these cells was not significant in males. Monocytes from females also displayed increased activation than males. In addition, females secreted significantly higher levels of IFN-α and IL-29 compared with males at 24 h. However, the situation was reversed at 1 week post stimulation and males displayed high levels of IFN-α production compared with females. Further investigations revealed that the secretion of CXCL-10, a chemokine associated with lung complications, was higher in males than females at 24 h. The PBMCs from females also displayed increased induction of CTLs. Altogether, our results suggest that decreased activation of pDCs, mDCs, and monocytes and the delayed and prolonged IFN-α secretion along with increased CXCL-10 secretion may be responsible for the increased morbidity and mortality of males to COVID-19.